Spatial distribution and risk identification of arsenic contamination in water and soil through GIS-based interpolation techniques in Jianghan Plain, Central China - Xiao, Tianyun; Muhammad, Akhtar Malik; Pan, Xiao; Wang, Yu; Guangming, Hu; Tang, Zhonghua (Frontiers in Environmental Science, 2022)
Investigating arsenic distribution in soil, surface water, and groundwater is interesting through correlation with local ecosystem factors and other hydrogeochemical parameters. The present study focused on several factors, which were population density, pumping rate, rain, land use, surface elevation, water level, and heavy metal contamination in the Jianghan plan. The arsenic contamination potential prediction map and categories were developed using various GIS techniques such as Ordinary Kriging and Quantile method. Then “Raster Calculator” tool was applied to verify the impact of the factors on arsenic concentration. Eighty-four single factor, bi-factors, and multi-factors models were established to investigate effective combinations among factors. Landuse and pumping rate factors were identified in the soil through an equal frequency tool, while in water population density and pumping rate were observed with high matching percentages. The arsenic concentration varied in groundwater 0.0001-0.1582mg/L , while in surface water between 0.0003- 0.05926mg/L and in soil sediments range 1.820 - 46.620mg/kg. Single factors showed the best equal frequency of arsenic concentration with waters of population density 68.62%, and in soil land use 65.57% and pumping 63.66%. Statistical calculation with percentage frequency factors also depicted a positive trend. The alkaline behavior of water bodies has an association with arsenic mobility. Elevated arsenic values in grids were observed along surface flow where high anthropogenic activities and urbanization. Additionally, a low concentration of Fe depicted reduction activities in the aquifer systems. Filtered drinking water and controlling arsenic suspected sources and factors which are affecting concentration in three phases will be options to reduce the health risk of the local population.